Migration as a Factor of the Sustainable Economic Development - Kurmaiev, Petro; Seliverstova, L.; Seliverstova, L.; Husarevych, N.; Kolisnichenko, P. (European Journal of Sustainable Development, 2020)
The problem of the interplay between migration and the achievement of the sustainable development goals is one of the main topics in modern scientific debate. The theoretical basis of the study is the understanding of migration as a continuous process caused by the interaction of a complex of factors, the result of which is the formation of a new quality globalized society. The methods used were: Comparative analysis and Content analysis. The authors note that the effectiveness of national policies depends significantly on the extent to which global migration trends are taken into account. The main factors that determine the dynamics of migration flows are identified in the article. The dominance of economic and security-humanitarian motives for migration is mentioned. It is noted that modern migration processes as a whole have a positive impact on the achievement of sustainable development goals. In modern world, migration is the driver of the country's demographic, economic and socio-cultural situation. For most countries in the world, the main objectives of immigration policy are to meet the need for labor, balance the labor markets, reduce the rate of depopulation and an aging population. The research made it possible to identify the types of immigration policy of governments of the world countries and their characteristics. The authors indicate that 73% of governments search to increase or maintain the current level of immigration of highly skilled workers. The thesis is substantiated that the impact of migrants on the wages of highly skilled workers in the country of destination is minimal. The impact of emigration on the socio-economic situation of the donor country is analyzed. The study found that emigration alone is not a destructive factor for the donor country. Significant deterioration in the country is influenced by a set of factors, among which migration is only one of them. Keywords: migration, sustainable economic development, donor-countries